Efektivitas Slow Deep Breathing terhadap Penurunan Tekanan Darah pada Lansia Penderita Hipertensi Primer - Zulkarnaini Zulkarnaini; Dara Febriana; Arista Ardilla (Holistic Nursing and Health Science, 2025)
Primary hypertension is the most common type of hypertension. Previous studies have proved the effect of slow deep breathing on reducing blood pressure however there was still limited study to examine the effect on primary hypertension particularly in elderly population. This study aimed to evaluate the effectiveness of slow deep breathing exercises in reducing blood pressure among older adults with primary hypertension. A quasi-experimental design with a one-group pretest-posttest approach was used in this study. A total of 16 participants were selected through purposive sampling from the elderly population in a village in Lhokseumawe City. Researchers conducted slow deep breathing 15 minutes during 5 day and blood pressure was measured manually using a sphygmomanometer and stethoscope. Data analysis was conducted using the Wilcoxon signed-rank method. The analysis indicated a statistically significant reduction in average systolic blood pressure, decreasing from 153.8 mmHg to 135 mmHg, along with a decline in diastolic pressure from 90 mmHg to 83.8 mmHg (p < 0.05). These results indicate the effectiveness of slow deep breathing exercises in decreasing blood pressure and may serve as an adjunct therapy for hypertensive elderly individuals. It is recommended that hypertensive older adults regularly practice this exercise in addition to taking prescribed medications to support blood pressure control.